Analisis Paparan Digital Fatigue Pada Generasi Z Untuk Mendukung Produktivitas Sehat di Era Digital - Sulistiono Sulistiono; Erna Wigati; Susilo Budi Winarno; Tuti Panghastuti (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
The excessive and uncontrolled intensity of Gen-Z in using digital media through various communication and information platforms can impact mental/physical health, resulting in unhealthy productivity in various spheres of activity. This study aims to analyze the causes, impacts, and solutions of digital media exposure on the aspect of digital fatigue which is expected to provide a new approach for Gen-Z to develop professional attitudes and mindsets in using digital media. The research method in this study uses a qualitative descriptive method. The sampling technique in this study uses purposive sampling and snowball sampling techniques. The purposive sampling technique is determined by the age range of Gen-Z from STIE Pariwisata API Yogyakarta students born between the mid-1990s and early 2010s. The snowball sampling technique used is all 129 students. Data analysis is carried out descriptively based on the percentage of respondents' assessments from the available questions. The results of this study are, the higher the percentage of counterproductive causes, impacts, and solutions to the digital fatigue aspects chosen by respondents, the more unhealthy productivity will result, conversely, the lower the percentage of counterproductive causes, impacts, and solutions to the digital fatigue aspects chosen by respondents, the more healthy productivity will result. The contribution of this study is, to support the success of activities carried out through the use of digital media in accessing information and communication channels, Gen-Z must be able to make proportional choices, namely choices that are oriented towards mental/physical health so that they can place Gen-Z in a healthy productivity environment.